2001
DOI: 10.1034/j.1600-0765.2001.360509.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin in gingival crevicular fluid

Abstract: Osteopontin (OPN) is a major glycosylated phosphoprotein in bone matrix and is produced by several cells including osteoblasts, osteoclasts and macrophages. OPN levels increase in active sites of bone metabolism. Recently, several bone-related proteins were identified in gingival crevicular fluid (GCF) to seek markers of alveolar bone resorption in periodontal disease. In this study, we investigated the existence of OPN in GCF and the correlation between OPN level in GCF and probing depth (PD) of sampling site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…25 Kido et al reported that OPN in GCF may be considered as a marker of alveolar bone loss in periodontitis, while Sharma and Pradeep reported that GCF OPN levels were higher in periodontitis patients compared to those with gingivitis and healthy subjects. 24,25 Conversely, the present study showed similar total amounts of OPN GCF levels in all geriatric groups. Neighboring tissues including alveolar bone and cementum, macrophages in periodontal tissues, blood and salivary glands function as the source of OPN in GCF.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…25 Kido et al reported that OPN in GCF may be considered as a marker of alveolar bone loss in periodontitis, while Sharma and Pradeep reported that GCF OPN levels were higher in periodontitis patients compared to those with gingivitis and healthy subjects. 24,25 Conversely, the present study showed similar total amounts of OPN GCF levels in all geriatric groups. Neighboring tissues including alveolar bone and cementum, macrophages in periodontal tissues, blood and salivary glands function as the source of OPN in GCF.…”
supporting
confidence: 49%
“…OPN, is mainly involved in enhancing osteoclastic action and has also been detected in GCF in some aforementioned studies. 24,25 The effects of initial periodontal therapy also confirmed that OPN levels significantly decreased and were correlated with decreasing clinical periodontal parameters. 25 Kido et al reported that OPN in GCF may be considered as a marker of alveolar bone loss in periodontitis, while Sharma and Pradeep reported that GCF OPN levels were higher in periodontitis patients compared to those with gingivitis and healthy subjects.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…The increased recognition of the interactions between the cells of the immune and skeletal system has led to the seeking of a variety of regulatory molecules that play a role in the progression of periodontal disease [25][26][27]. In previous studies, the bestknown markers of the bone turnover have been widely investigated in GCF samples of patients with different periodontal diseases and implicated to be associated with the progression of periodontal diseases [28][29][30]. Several investigations provided contradictory evidence about the role of osteocalcin in GCF of patients with periodontitis [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations on OPN indicated that OPN concentrations in gingival crevicular fluid increased proportionally with the progression of disease; and OPN levels in GCF were significantly reduced following nonsurgical periodontal treatment (33,34).…”
Section: Markers Of Alveolar Bone Lossmentioning
confidence: 99%